Testing Wagner's Law in the presence of Structural Changes: New Evidence from Six African Countries (1960-2013) - Keho, Yaya (International Journal of Economics and Financial Issues, 2016)
This study re-examines the relationship between government expenditure and national income in order to test the validity of Wagner's law for six African countries over the period from 1960 to 2013. The empirical analysis uses the Gregory and Hansen (1996) cointegration test which allows for a structural break in the long run relationships. We find supporting evidence of Wagner's law in Ghana over the period 1960-2013 and in Cote d'Ivoire for the period 1960-1995. Evidence for Kenya for the period 1960-1991 supports both Wagner's law and Keynesian view. The results for the other three countries do not advocate Wagner's law or its reverse in the long run. Keywords: Wagner's law; Structural change; GDP; Cointegration; Granger causality. JEL Classifications: C32; E62 ; H50 ; O55